Jojaro (Pemuda) dan Mongare (Pemudi) Melalui Peningkatan Pengetahuan TBC Sebagai Upaya Preventif - Talarima, Bellytra; Lawalata, Ivy Violan; Jotlely, Hery (Jurnal SOLMA, 2024)
Background: Based on the Global Tuberculosis Report in 2022, the prevalence of TB in Indonesia is 10.6 million, Ambon City is an area in Maluku Province with the highest incidence of TB, namely 4,787 cases with the highest locus in the Passo community health center area in Ama Ory Hamlet. The aim was to increase the knowledge of jojora and mongare (young men and women) about TB, ILTB and TPT. Method The method used is community education through a counseling approach to increase knowledge by delivering material (lectures). Result: Respondents experienced an increase in knowledge where the first session of pre test results 68.4 and post test 87.6 there was an increase of 19.2 and the second session of pre test results 45.7 and post test results 69.8 there was an increase of 24.1. Conclusion: There was an increase in knowledge among respondents after counseling was conducted.